Rods extraction sequence to optimize the neutron flux in irradiation facilities at Peruvian Research Reactor RP-10 - Vela, Mariano (2007)
In this work we evaluate the effect of two different extraction sequences of control and emergency rods on neutron flux distribution in core at Peruvian Research Reactor RP-10. The method applied was to irradiate small gold foils in the irradiation facilities of the core to carry out the nuclear reaction 197-Au(n,γ)198-Au; then using a gamma spectrometry system and the Westcott formalism we obtained the neutron flux. The results confirm the favourable effect of the configuration of emergency and control rods, increasing the neutron flux both thermal and epithermal neutron flux; near to 25 % in the central irradiation facilities and near to 50 % for the other irradiation facilities. The results entail to know better the neutron flux distribution for certain control and emergency rod configuration; so we can optimize the neutron flux and irradiation time for a certain power of operation and consequently to economize energy and fuel consumption.